2015
DOI: 10.1016/j.pmedr.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine initiation among 9–13-year-olds in the United States

Abstract: Objective The quadrivalent and 9-valent human papillomavirus (HPV) vaccines are licensed for administration among 9–26-year-old males and females, with routine vaccination recommended for 11–12-year-olds. Despite the availability of the vaccine at younger ages, few studies have explored vaccine uptake prior to age 13, and national HPV vaccination surveillance data is limited to 13–17-year-olds. Our objective was to examine rates and predictors of HPV vaccine initiation among 9–13-year-olds in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 31 publications
(35 reference statements)
1
43
1
Order By: Relevance
“…11 In addition to parents, healthcare providers play a crucial role in ensuring its administration. [21][22][23][24][25][26][27][28] It is important for healthcare providers to bundle HPV vaccines with other required vaccines, such as tetanus-diphtheria-pertussis (Tdap) and meningococcal vaccine (MCV4, MenB). 29,30 They are encouraged to consistently and equally recommend HPV vaccination to parents of female and male children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition to parents, healthcare providers play a crucial role in ensuring its administration. [21][22][23][24][25][26][27][28] It is important for healthcare providers to bundle HPV vaccines with other required vaccines, such as tetanus-diphtheria-pertussis (Tdap) and meningococcal vaccine (MCV4, MenB). 29,30 They are encouraged to consistently and equally recommend HPV vaccination to parents of female and male children.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] A recent survey of Texas healthcare providers found that 94% self-reported giving a consistent recommendation of HPV vaccination to 9-12-year-old children of both sexes. 34 Factors associated with vaccine uptake Factors shown to be positively associated with parents' uptake of HPV vaccines for their children include: (1) healthcare providerphysician recommendation and parents' trust in healthcare providers, 20,21,25,26,33 (2) mother as HPV vaccine decision-maker versus both parents, 20 (3) parents' vaccine beliefs, attitudes, and intentions, 20,35 (4) preventive healthcare utilization for child, 28 (5) insurance / costhealth insurance coverage of HPV vaccination, 28 (6) parents' HPV risk history, 20 7parents' HPV-related knowledge and awareness, 28 and (8) sociodemographic factorsurban versus rural location and child's age. 20,21,25,26,33 For those who have chosen to not vaccinate against HPV, parents cite lack of knowledge and worry about the side effects or safety of the vaccine as the primary reasons for vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…This cannot be the case for HPV vaccination: The lack of any medical indication for vaccinating very young children against HPV, together with the understanding that vaccination should begin prior to sexual activity, led policymakers to target HPV vaccination to boys and girls between the ages of 9–13 years [36]. In most countries HPV vaccination is conducted on youngsters at the higher age range of 12–13.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated that an additional 6.77 million girls and an additional 7.62 million boys aged 11 to 12 years would need to receive 2 doses of the vaccine between 2018 and 2026 for 80% prevalence to be achieved by 2026. [21][22][23][24][25] Providers cite several barriers to recommending HPVV, including incomplete knowledge of the vaccine's benefits, parental hesitancy, and anticipated parental refusal or deferment, and some providers base recommendations on perceived risk. Population growth contributed minimally to the number needing vaccination in future birth cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…We could not ascertain whether a provider recommendation was given during these visits; however, only 55% of parents reported that they had ever received a recommendation to vaccinate their child against HPV, and previous studies show that opportunities to endorse and administer HPVV during clinical visits are often missed. [21][22][23][24][25] Providers cite several barriers to recommending HPVV, including incomplete knowledge of the vaccine's benefits, parental hesitancy, and anticipated parental refusal or deferment, and some providers base recommendations on perceived risk. 22,[26][27][28][29] These barriers may be particularly prominent in our study population because some providers may anticipate greater parental refusal and discomfort with discussing a sexually transmitted infection in younger patients, and others may not be aware of the recommended age for initiating the vaccine.…”
Section: Discussionmentioning
confidence: 99%